THE UTILIZATION OF TIKTOK FOR LEARNING MOTIVATION AND LANGUAGE MASTERY - Soeharto, Dhea Vaniastuti; Murniati, Cecilia Titiek (Universitas 17 Agustus 1945 Semarang, 2024)
Current literature on the utilization of TikTok reveals the potentials of TikTok in English language education. As one of the most popular social media applications, TikTok has currently gained popularity. The role of TikTok in the field of education remains an interesting issue to study. The research questions in this study were twofold: first, to investigate the social and interactive features of TikTok commonly used by students, and second, to investigate the perceived benefits of integrating TikTok as a learning tool for English as a Foreign Language development. The respondents for this study were students from 18 private and state universities in Indonesia. The data were collected through online questionnaires administered to 101 respondents. The research findings revealed that students generally have a positive view of TikTok as a platform to improve their English language skills. TikTok is recognized not only as an entertaining medium but also as a valuable tool for language learning. Its social and interactive features allow students to create content and participate in discussions of common interests actively. Thus, users can utilize the features and at the same time improve their English skills. In addition, this application has the potential to increase students’ learning motivation to learn English language.